2020
DOI: 10.1002/art.41078
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps in Tissue and Periphery in Juvenile Dermatomyositis

Abstract: Objective. Neutrophils are key immune cells participating in host defense through several mechanisms, including the formation of neutrophil extracellular traps (NETs). This study was undertaken to investigate the role of neutrophils in juvenile dermatomyositis (JDM).Methods. Electron microscopy was used to identify neutrophils in tissue. NETs were also imaged using fluorescence microscopy and quantified using a myeloperoxidase-DNA enzyme-linked immunosorbent assay (ELISA) in plasma obtained from healthy childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 48 publications
4
53
0
1
Order By: Relevance
“…Indeed, previous observations have suggested that impaired NET degradation may also contribute to ILD in IIM (31). Similarly, a recent study reported a link between calcium deposition in tissues, the calcinosis characteristic of JDM, and the development of neutrophil activation and NETs in muscle tissue (15). This may be an additional mechanism that induces NET formation in these individuals.…”
Section: Gene Expression (Fold Change) and Q Values Of 5 Neutrophilmentioning
confidence: 78%
See 1 more Smart Citation
“…Indeed, previous observations have suggested that impaired NET degradation may also contribute to ILD in IIM (31). Similarly, a recent study reported a link between calcium deposition in tissues, the calcinosis characteristic of JDM, and the development of neutrophil activation and NETs in muscle tissue (15). This may be an additional mechanism that induces NET formation in these individuals.…”
Section: Gene Expression (Fold Change) and Q Values Of 5 Neutrophilmentioning
confidence: 78%
“…A previous study in the Chinese population reported that NETs are associated with ILD in IIM, particularly in subjects who are positive for anti-MDA5 autoantibodies (14), indicating that neutrophils potentially may be involved in the pathogenesis of this group of conditions. Furthermore, a recent association among circulating NETs, neutrophil activation, and calcinosis in juvenile DM (JDM) has been described, implicating calcium deposits characteristic of this disease with the induction of tissue and peripheral NET formation (15).However, whether aberrant neutrophil responses and NET formation play an important role in IIM and associated muscle damage remains to be systematically studied. Here, we investigated whether neutrophil dysregulation is prevalent in IIM and examined its associations with clinical manifestations and immune perturbances as well as its potential role in muscle damage.…”
Section: Introductionmentioning
confidence: 99%
“…That group included TSP-4, Il-23, VCAM-1 and CD48 and fibrinogen. Of note, CD48 binds to the natural killer cell ligand 284; natural killer cells have recently been more rigorously implicated in JDM tissue damage [40], while polymorphonuclear cells have also been recently identified [41].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed the involvement of complement in muscle biopsies from JDM patients [43];further investigation is needed to establish the physiological significance of these circulating complement factors in JDM. Not only may complement be bound to circulating immune complexes, present in JDM plasma, [41], but the levels of C4 may be decreased as a consequence of decreased gene copy number [43].…”
Section: Discussionmentioning
confidence: 99%
“…The IgG ICs induce NET release after binding to FcgRIIA on neutrophils (8,9). The capacity of ICs and inflammatory cytokines to induce NET formation is consistent with excessive NET formation being observed in several autoimmune and inflammatory conditions, including gout, rheumatoid arthritis (RA), psoriasis, systemic lupus erythematosus (SLE), juvenile dermatomyositis (JDM), and antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) with levels of NETs often linked to disease activity and severity (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 72%